Dynamic Response Characteristics of the Structures under Excavation by High-Efficiency Blasting in the Urban Ultradeep Foundation Pit - Zhen Lei; Qing Chen; Wen Zhao; Yu-Jing Li; Zheng-Hua Gao (Shock and Vibration)
To ensure the safe and efficient excavation of ultradeep foundation pits in a complex urban environment, the ultradeep foundation pit excavation project of Liuguangmen Urban Complex in Guiyang City was taken as the study point. A high-efficiency blasting method was proposed for the excavation of vibration-isolating slot and electronic detonators, and a three-dimensional spatial calculation model of the foundation pit structure was established. In addition, the field test and numerical simulation of the blasting vibration were developed. The feasibility of the high-efficiency blasting method was demonstrated, and the propagation law of the dynamic response characteristic parameters of the structure was explored using an electronic detonator and vibration-isolating slot. The results show that the electronic detonator carried out peak shaving within the group, unloading waves between the groups, and the blocking effect of the vibration-isolating slot, and all these effectively reduced the peak stress and peak particle vibration velocity, evenly distributed the vibration velocity, and guaranteed the safety of the surrounding existing buildings, proving the feasibility of the efficient blasting method. There is a “wall effect” at the supporting pile, whose propagation velocity is lower than that inside the rock mass, and the PPV is radial X > tangential Y > vertical Z. The peak values of stress, strain, and PPV all decrease with increasing supporting pile height, and there is an inflection point at 20 m. The internal nodes of the pile reciprocate without sharp change and failure in displacement. The peak displacement of different nodes is in the order X > Y > Z with increasing pile height, and the maximum peak value is 0.08 mm.